2004
DOI: 10.1177/1532673x03260353
|View full text |Cite
|
Sign up to set email alerts
|

The Calculus of Concession

Abstract: In this research we outline and evaluate a theory of the "calculus of concession": when and why presidential primary candidates exit the race. Our explanation builds on prior studies of candidate attrition that traditionally emphasize money. However, we focus additional attention on the role of the press and its potential to influence a candidate's exit decision. Data from the 2000 Republican presidential nomination campaign are used to test a Weibull model of candidate exit. Our results suggest that money is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…First, candidates who receive a significant amount of 7 DOI: 10.15763/issn.2374-779X.2020.37.2.1-28 media attention tend to stay in the race longer (Fei Shen 2008). Second, media attention can help long-shot candidates stay in a primary when they lag the frontrunners in other resources (Haynes et al 2004;Haynes, Flowers, and Gurian 2002). Finally, media attention helps candidate performance in both Iowa and New Hampshire (Donovan and Hunsaker 2009).…”
Section: Mediamentioning
confidence: 99%
“…First, candidates who receive a significant amount of 7 DOI: 10.15763/issn.2374-779X.2020.37.2.1-28 media attention tend to stay in the race longer (Fei Shen 2008). Second, media attention can help long-shot candidates stay in a primary when they lag the frontrunners in other resources (Haynes et al 2004;Haynes, Flowers, and Gurian 2002). Finally, media attention helps candidate performance in both Iowa and New Hampshire (Donovan and Hunsaker 2009).…”
Section: Mediamentioning
confidence: 99%
“…Damore (1997) determined there were similar effects relating to the media's coverage and fundraising, but found that the impact was far greater for longshot candidates. Haynes et al (2004) determined that news coverage is far more critical to the winnowing decisions of longshots early in the campaign even if they have limited resources. Moreover, news coverage has more of an impact when the race is more dynamic.…”
Section: The Horserace Framementioning
confidence: 99%
“…Nomination campaigns have become increasingly front‐loaded, compressed, and nationalized (Mayer and Busch 2004), making the preprimary campaign, or what is also termed the invisible primary or the exhibition season, a powerful force in the selection of party nominees for president. Indeed candidates for nomination often withdraw in this period, and party nominations are clinched within, what was until recently, mostly shorter and shorter time periods (Haynes et al. 2004; Norrander 2006).…”
mentioning
confidence: 99%
“…nation campaigns have become increasingly front-loaded, compressed, and nationalized (Mayer and Busch 2004), making the preprimary campaign, or what is also termed the invisible primary or the exhibition season, a powerful force in the selection of party nominees for president. Indeed candidates for nomination often withdraw in this period, and party nominations are clinched within, what was until recently, mostly shorter and shorter time periods (Haynes et al 2004;Norrander 2006). Recent scholarship now emphasizes that a candidate's level of funding and national political support at the beginning of the primary season largely determine who wins the nomination Dowdle 2001, 2005;Cohen et al 2008;Mayer 1996Mayer , 2003Steger et al 2004;Steger 2007).…”
mentioning
confidence: 99%